Rancang Bangun Kursi Roda Bermotor Elektrik Dengan Sistem Pengendalian Gestur Untuk Penyandang Tetraplegic - Marten Darmawan; Joseph Fernando Budi Prasetyo; Arka Dwinanda Soewono (Journal of Science and Applicative Technology, 2023)
Improving medical services is continuously prioritized for the sake of achieving the welfare of all people in the world, and by providing good services in the medical field, people's needs will be increasingly fulfilled. Limitations of movement in someone with a disability, such as persons with disabilities tetraplegic in terms of mobility, are often obstacles. Therefore, a media-assisting movement is needed. This study designed an electric wheelchair that can help users with disabilities tetraplegic in moving without the need for too much force as in a standard wheelchair. This electric wheelchair uses automation by utilizing Accelerometer, which can detect vectors or so-called gyroscopes and connect with Arduino as the processor is continued to the DC motor as the driving force. Based on the test data, it was found that the design of this wheelchair moves as desired. This can be seen from the change in speed of the driving motor to changes in the tilt of the accelerometer mounted on the head. In the forward motion test, the maximum motor speed is 35 RPM when the accelerometer angle is at a slope of 64.7o positive axes. Meanwhile, the backward movement of the wheelchair occurs when the accelerometer is at a slope of -21.1o and produces a speed of 11.2 RPM on wheels. The rider's maximum load is designed to be 50 Kg.